Individual resection and reconstruction of pelvic tumor with three-dimensional printed customized hemi-pelvic prosthesis: A case report. Issue 36 (September 2019) - Han, Qing; Zhang, Kesong; Zhang, Yong; Wang, Chenyu; Yang, Kerong; Zou, Yun; Chen, Bingpeng; Wang, Jincheng
Abstract: Rationale: Pelvic tumor had great impact on patients' quality of life. After tumor resection, how to accurately fill bone defect remained challenging for orthopedic surgeons. Due to lack of individual design, high incidence of prosthetic mismatching, and loosening were reported in pelvic reconstruction surgery with conventional modular prostheses. Nowadays, with rapid development of three-dimensional (3D) print technology, pelvic prostheses could be designed according to patients' own anatomy. The objective of this study was to describe the application of 3D printed customized hemi-pelvic prosthesis for patients with pelvic tumor. Patient concerns: A 62-year-old female had developed severe right joint pain without obvious inducement from 5 months before she sought medical advice. Pain, swelling, and limited range of motion of right joint were founded during physical examination. Diagnosis: The patients were diagnosed as "right acetabulum metastatic carcinoma" Intervention: 3D printed titanium alloy hemi-pelvic prosthesis was designed according the morphology of unaffected side hemi-pelvis and subsequently implanted in surgery to reconstruct the pelvis. 3D printed osteotomy guide and pelvic model were also manufactured and applied to improve accuracy of osteotomy and reduce operation time. X-Ray of pelvis, Harris score, musculoskeletal tumor society score (MSTS) and The MOS item short from health survey (SF-36) were recorded during the period of preoperation, 1, 3, 6, 12 months follow-up after operation. Outcomes: 3D printed hemi-pelvic prosthesis matched precisely with pelvis and implanted successfully. There was no sign of prosthetic loosening within 12 months' follow-up. No sign of peri-prosthetic infection from laboratory examination. Harris score, MSTS, and SF-36 were gradually increasing during follow-up period. Lessons: Satisfactory effect of pelvic reconstruction could be achieved by 3D printed hemi-pelvic prostheses. It also provided a promising way to the treatment of pelvic tumor in similar cases.